A Abordagem Intercultural nas Escolas Indígenas Tikuna do Amazonas: o Ensino de Química - Monteiro, Ercila Pinto; Zuliani, Silvia Regina Quijadas Aro [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2020)
This article is part of doctoral work that sought to understand the teaching of chemistry in Tikuna schools of Amazonas and their claims, in order to ensure that this teaching is intercultural. A field study was carried out for six months in the region of Alto Solimões, Amazonas, Brazil, when the school routine of Tikuna teachers was observed in the area of chemistry, with the intention of understanding the teaching approach, planning, teachers' interests and challenges. In addition, teachers were interviewed, and shared the purposes and challenges of making chemistry teaching intercultural. The results show that, in Tikuna schools, the teaching of chemistry reproduces the passivity, the centrality of knowledge in teachers, and massive teaching. During the interview, the indigenous people understand that the teaching of differential and intercultural chemistry will only take place when traditional knowledge is integrated into the school, in a way that is articulated with global knowledge.

Este artigo é uma seção do doutorado que procurou compreender o ensino da química nas escolas de Tikuna do Amazonas e as suas reivindicações, a fim de assegurar que este ensino seja intercultural. Para tal, foi realizado um estudo de campo durante seis meses na região do Alto Solimões, Amazonas, sendo observada a rotina dos professores de química com a intenção de compreender a abordagem pedagógica, o planeamento, os seus interesses e desafios. Além disso, os professores nos concederam entrevistas, compartilhando os propósitos e os desafios de tornar intercultural o ensino da química. Os resultados mostram que nas escolas de Tikuna o ensino da química reproduz a passividade, a centralidade do conhecimento nos professores e o ensino livresco. Em entrevista, os povos indígenas compreendem que o ensino da química diferencial e intercultural só terá lugar quando o conhecimento tradicional estiver integrado na escola, de uma forma articulada com o conhecimento global.
The Intercultural Approach in Tikuna Amazonas Indigenous Schools: Teaching Chemistry
Keywords: Intercultural education; Science education; Indigenous school education; Chemistry teaching; Educação intercultural; Educação científica; Educação escolar indígena; Ensino de química